Pope Benedict XVI and the politics of modernity - Guerra, Marc D. eeditor (Routledge/Taylor & Francis Group, 2014)
Focusing on Pope Benedict XVI's nuanced account as to why the modern West cannot currently afford to forget or neglect its premodern Hellenic and Christian roots, this book will interest religious and nonreligious people who are concerned about the future of democracy and religion in contemporary Western societies. This book was based on a special issue of Perpsectives on Political Science.